Three-dimensional carbon governance for the 2035 carbon target: Spatial carbon efficiency and decarbonization pathways of urban construction land in Nanjing, China - Xinxian Qi; Yanfeng Di; Peng Pan; Geng Liu; Tianyu Wang; Honghui Zhang; Xianjin Huang (Sustainable Cities and Society, 2026)

Visible-light-driven CuVO/biochar composite activates periodate for efficient diclofenac degradation: Unveiling the electron-shuttling mechanism of p-benzoquinone - Yuxin liu; Wen Tan; Sinuo Gong; Yang Guo; Jingyi Zhu; Honghui Pan; Qin Shi; Shiyong Huang; Ziyin Li; Chuanqi Zhao (Journal of Environmental Chemical Engineering, 2026)

Insight into peroxymonosulfate activation by biochar-derived dissolved organic matter toward in-situ sustainable groundwater remediation: The role of active functional groups and efficient electron shuttles - Xinling Ye; Chenxi Wang; Qin Shi; Chuanqi Zhao; Honghui Pan; Yan Liu; Xixiang Liu (Journal of Cleaner Production, 2026)

Citric acid-assisted MnOx/biochar for periodate activation and diclofenac degradation: A non-radical pathway driven by Mn(III) stabilization - Wen Tan; Yuxin liu; Sinuo Gong; Yang Guo; Jingyi Zhu; Honghui Pan; Qin Shi; Ziyin Li; Chuanqi Zhao (Journal of Environmental Management, 2026)

Treatment of Kiwifruit with Bacillus subtilis LS11 postharvest mitigates disease occurrence and alters its microbiome - Huiyun Song; Zhihao Duan; Jian Yang; BeiBei Liang; Honghui Shi; Xiaoling Wang; Zhu Gao; Liuyi Pan; Jipeng Mao; Xuchen Gong; Dongliang Yao; Mengfei Lin (Postharvest Biology and Technology, 2026)

Photocatalytic degradation of diclofenac using aluminium oxide modified photocatalyst derived from iron-rich sludge - Chenxu Wang; Shihao Ni; Yan Liu; Honghui Pan; Qin Shi; Chuanqi Zhao; Xixiang Liu (Journal of Environmental Chemical Engineering, 2025)

miR-125b Orchestrates the Proliferation and Fusion of Myoblasts in Chinese Perch by Targeting the MyoD and Myomaker - Xin Zhu; Wei Zeng; Yangyang Meng; Yaxiong Pan; Honghui Li; Lingsheng Bao; Jianshe Zhang; Wuying Chu (Marine Biotechnology, 2025)

Extreme Wetness Reduces Soil Microbial Residue Carbon More Substantially Than Extreme Drought Across Grassland Ecosystems - Yingchao Yu; Shuang Liu; Junxiao Pan; Juntao Zhu; Ning Zong; Xinyuan Zhang; Honghui Wu; Hui An; Huajie Diao; Xiaoan Zuo; Cunzheng Wei; Fawei Zhang; et al. (Global Change Biology, 2025)
Soil microbial residue carbon (MRC) represents a significant component of soil carbon pools and regulates the response of soil carbon sequestration to precipitation changes. However, the response of soil MRC to extreme drought and wetness and the underlying mechanisms in regional grassland ecosystems remain unclear. Here, we quantified the responses of soil MRC content to extreme drought and wetness and identified the key drivers using a coordinated precipitation change experiment across nine alpine and temperate grassland ecosystems in China. Extreme drought (−50% precipitation) reduced MRC content by 8% on average. In contrast, extreme wetness (+50% precipitation) unexpectedly caused a pronounced 24% average decline in MRC content. Under extreme drought, reduced plant biomass inhibited soil MRC formation, and soil microbial N enzyme activity accelerated soil MRC decomposition. Moreover, wetter ecosystems exhibited greater losses of soil MRC, whereas drier ecosystems experienced a smaller decline. Under extreme wetness, increased soil microbial N enzyme activity accelerated the decomposition and utilization of microbial residue due to intensified microbial nitrogen limitation, resulting in a reduction in MRC. Our findings challenged the conventional understanding that extreme wetness promotes MRC accumulation by revealing a stronger reduction in MRC content under extreme wetness than under extreme drought. By uncovering distinct mechanisms driving MRC responses to extreme drought and wetness, our study provides critical insights into the dynamics of microbial‐derived carbon in grassland ecosystems under future climate change.

Insight into in-situ Fenton-like catalysis by iron-rich sludge-derived iron-carbon composites: Molecular oxygen activation driven by electron transfer in Fe-C structure - Zhuowen Li; Liying Liang; Wen Tan; Yan Liu; Honghui Pan; Qin Shi; Chuanqi Zhao; Shiyong Huang; Xixiang Liu (Journal of Environmental Chemical Engineering, 2025)

Visible light-driven copper vanadate/biochar nanocomposite for heterogeneous photocatalysis degradation of tetracycline: Performance, mechanism, and application of machine learning - Yuxuan Chen; Chuanqi Zhao; Wen Tan; Sinuo Gong; Honghui Pan; Xixiang Liu; Shiyong Huang; Qin Shi (Environmental Research, 2025)

The zinc-finger transcription factor ZFP8 negatively regulates the drought stress response in Arabidopsis thaliana by inhibiting the transcriptional activity of ABF2 - Yu'ang Tian; Yanling Li; Kelan Wang; Ran Xia; Yingru Lin; Guohui Pan; Haoyu Shi; Dawei Zhang; Honghui Lin (Journal of Plant Physiology, 2024)

Insight into the sulfite activation by Fe-rich sludge-derived biochar for efficient organic contaminant degradation: The role of iron species - Xixiang Liu; Xinyi Shi; Mingjian Huang; Honghui Pan; Yan Liu; Liying Liang; Chuanqi Zhao; Shiyong Huang; Tieguang He (Journal of Water Process Engineering, 2024)

Enhanced dewaterability of waste activated sludge via peroxymonosulfate activation process initiated by magnetic biochar derived from iron-rich sludge - Xixiang Liu; Fuyu Luo; Liying Liang; Nan Li; Zheng Zhou; Yan Liu; Honghui Pan (Sustainable Chemistry and Pharmacy, 2024)

Factors controlling the contributions of bacterial and fungal residue carbon to soil organic carbon in grassland ecosystems - Yingchao Yu; Junxiao Pan; Honghui Wu; Juntao Zhu; Ning Zong; Hui An; Changhui Wang; Xiaoan Zuo; Cunzheng Wei; Fawei Zhang; Shuang Liu; Jielin Liu; et al. (CATENA, 2024)

Self-endowed magnetic photocatalysts derived from iron-rich sludge and its recycling in photocatalytic process for tetracycline degradation - Xixiang Liu; Hengyi Wang; Chenxu Wang; Liyang Zhao; Honghui Pan; Yan Liu; Liying Liang; Chuanqi Zhao; Shiyong Huang (Bioresource Technology, 2024)

Natural grass coverage enriches arbuscular mycorrhizal fungal communities in subtropical citrus orchards through the regulation of Glomus on a regional scale - Zengwei Feng; Chengxiang Pan; Yongqiang Qin; Xiaolin Xie; Xiaodi Liu; Meng Chen; Wei Zhang; Honghui Zhu; Qing Yao (Applied Soil Ecology, 2024)

Numerical and experimental investigation of 3D flow field bipolar plates for PEMFCs by metal 3D printing - Kaijie Lu; Jian Zhang; Honghui Ding; Zhenhao Wang; Xiaoming Pan (Fuel, 2024)

Efficiently Removal of Tetracycline from Water by Fe3O4-sludge Biochar - Liyang Zhao; Peixi He; Qian Li; Honghui Pan; Ting Xie; Shiyong Huang; Shaohua Cao; Xixiang Liu (Water, Air, & Soil Pollution, 2024)

Spatial and temporal distribution of fish egg communities in the adjacent waters of Daya Bay nuclear power plant and their relationship with environmental factors - Zhen Tan; Fengxia Wu; Yiyong Rao; Chuanhao Pan; Gang Hou; Honghui Huang (Frontiers in Marine Science, 2023)
The thermal discharge of Daya Bay Nuclear Power Plant has a certain impact on the ecological environment of the adjacent waters. In order to understand and evaluate changes in the fish egg community structure in the adjacent waters of Daya Bay Nuclear Power Plant and their relationship with environmental factors, four surveys were conducted to investigate fish eggs in January (winter), March (spring), August (summer) and November (autumn) of 2020. A total of 100,985 fish eggs were collected and 17 taxa were identified, belonging to five orders, 14 families and 17 genera. Among them, Perciformes and Clupeiformes were the main contributing taxa to fish egg species and abundance in the waters adjacent to Daya Bay Nuclear Power Plant. The number of fish egg species ranged from high to low was summer, spring, autumn and winter; the average abundance ranged from high to low was spring, summer, winter and autumn. The results showed that except in winter, the average abundance of fish eggs was greater in northeast area than in southwest area. The Shannon-Weiner species diversity index ( H’ ), Pielou evenness index ( J’ ) and Margalef richness index ( d ) were significantly different between seasons, but none were significantly different between areas. The results of NMDS analysis showed that there were significant differences in fish egg communities between seasons. Surface seawater temperature the average abundance of fish eggs was positively correlated in the results of all four seasons. Although the entrainment effect of nuclear power plant water intake and thermal pollution of partial waters owing to thermal discharge can cause some loss of fish eggs, fish resources can still be effectively maintained.

Efficient photocatalytic degradation of tetracycline using magnetic biochar derived by iron-rich sludge - Xixiang Liu; Hengyi Wang; Xinyi Shi; Zheng Zhou; Nan Li; Honghui Pan; Qin Shi (Environmental Science and Pollution Research, 2023)

Research on wind power industrial policies’ functional mechanism to the quality of enterprise innovation - Xiaozhen Wang; Ziyang Tao; Gonghe Pan; Honghui Zou; Ying Xie; Xiaolei Li (Environmental Science and Pollution Research, 2022)

Monitoring tilting angle of the slope surface to predict loess fall landslide: an on-site evidence from Heifangtai loess fall landslide in Gansu Province, China - Honghui Wang; Pan Zhong; Dehao Xiu; Yunshun Zhong; Dalei Peng; Qiang Xu (Landslides, 2022)

Temporal and spatial distribution characteristics of irrigation water requirement for main crops in the plain area of Hebei Province* - Minghan Cheng; Xiyun Jiao; Weihua Guo; Shufang Wang; Yanchuan Pan; Hang Zhang; Honghui Sang (Irrigation and Drainage, 2020)
The spatial and temporal distribution of agricultural water requirement can provide a scientific basis for regional drought and disaster mitigation management and optimal allocation of irrigation water resources. The irrigation water requirement and irrigation water requirement index of the Hebei Plain during 57 years were calculated by a long series of data of 22 weather stations from 1961 to 2017, and the spatial and temporal distribution characteristics were also analysed. The results show that (a) in this long‐term series, the irrigation water requirement was between 164 and 759 mm, and the irrigation water requirement index was between 0.33 and 0.78, which fluctuated between 1961 and 2017, and in 1977 began to show a downward trend; (b) irrigation water requirement and irrigation water requirement index in the Hebei Plain area had obvious seasonal changes during the year. Irrigation water requirement and irrigation water requirement index were the largest in April, the reasons for this phenomenon being high evapotranspiration and low effective precipitation; (c) the spatial distribution of irrigation water requirement and irrigation water requirement index in the Hebei Plain area are significantly different, both of which are larger in the central region and smaller in the Northeast and Southwest regions.

Effects of Starvation on Antioxidant-Related Signaling Molecules, Oxidative Stress, and Autophagy in Juvenile Chinese Perch Skeletal Muscle - Ping Wu; Aimin Wang; Jia Cheng; Lin Chen; Yaxiong Pan; Honghui Li; Qi Zhang; Jiaqi Zhang; Wuying Chu; Jianshe Zhang (Marine Biotechnology, 2020)

Correction to: Heat stress alters genome-wide profiles of circular RNAs in Arabidopsis - Ting Pan; Xiuqiang Sun; Yangxuan Liu; Hui Li; Guangbing Deng; Honghui Lin; Songhu Wang (Plant Molecular Biology, 2018)

Heat stress alters genome-wide profiles of circular RNAs in Arabidopsis - Ting Pan; Xiuqiang Sun; Yangxuan Liu; Hui Li; Guangbin Deng; Honghui Lin; Songhu Wang (Plant Molecular Biology, 2018)